The misuse of word order in the writing of jordanian efl learners / Mohammad Hamad Khalef Alkresheh - Khalef Alkresheh, Mohammad Hamad (2013)

(untitled)
Like any other learning process, learning a new language might be accompanied with various problems, which includes errors. Errors may be considered as markers of the learner's transitional competence. They are considered an obligatory feature of the learning process. Besides, they can provide evidence with regard to the system of the language that L2/FL learners are using or have learnt at a particular point throughout the language learning process. By analysing errors in learners' written production, it is probable that strategies employed in their SLA may be discovered (Ellis, 2008; Lim, 2010; Al-Khresheh, 2011; Al-Qudah, 2012). Among the areas where Jordanian learners of English face much difficulty while writing in English is mostly in word order. It has always been a source of great difficulty, not only for Jordanian learners, but also for learners from other linguistic backgrounds. The use of English L2 word order by Jordanian EFL learners can be very challenging at times. While there is much research done on the acquisition of English as a FL by Arab learners, the literature suggests that there is limited research on the misuse of word order. This fact has been clearly acknowledged by several researchers who declared that word order has not been given enough attention. Therefore, this study was aimed to fill that gap through an in-depth investigation on word order use by Jordanian EFL learners. Specifically, this study aimed at identifying the linguistic factors causing errors in the use of word order, namely: interlingual and intralingual interference. It also aimed at identifying the most common English L2 word order errors and comprising them under a linguistic taxonomy, based on the linguistic category taxonomy. Identification of word order similarities and differences between the subjects' L1 and L2 was also carried out by this study. To achieve the main iv objectives, a composition test was carried out on a group of 447 Jordanian school students. Following the producers of Error Analysis approach, the data was collocated, analysed and explained. The findings of the study confirmed that English and Arabic are completely different from one another with respect to word order. While English shows a rigid order in its grammatical and syntactic structures, Arabic has a rather free choice. Secondly, the findings also suggested that both interlingual and intralingual interference possess their own linguistic effect on the process of SLA. These were major problems for the present subjects in their use of English L2 word order structures. Thirdly, the subjects committed a total of 2331 word order errors. Of these, 1179 errors were due to interlingual interference from subjects' L1. The remaining 1152 word order errors were ascribed to intralingual interference from the subjects' TL itself. Fourthly, the most common types of English L2 word order errors made by subjects were identified and classified into various grammatical categories. The process of identification as well as analysis was based on a data-driven approach. On the basis of these findings, pedagogical implications were discussed and a list of noteworthy recommendations for further research was put forward.